Implementation of Buck-Boost Converter as Low Voltage Stabilizer at 15 V - Suwarno Suwarno; Tole Sutikno (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper presents the implementation of the buck-boost converter design which is a power electronics applications that can stabilize voltage, even though the input voltage changes. Regulator to stabilize the voltage using PWM pulse that triger pin 2 on XL6009. In this design of buck-boost converter is implemented using the XL6009, LM7815 and TIP2955. LM7815 as output voltage regulator at 15V with 1A output current, while TIP2955 is able to overcome output current up to 5A. When the LM7815 and TIP2955 are connected in parallel, the converter can increase the output current to 6A.. Testing is done using varied voltage sources that can be set. The results obtained from this design can be applied to PV (Photovoltaic) and WP (Wind Power), with changes in input voltage between 3-21V dc can produce output voltage 15V.